Reflection of the Competitive Pressures on Strategic Performance : Field Research in a sample of Iraqi private commercial banks (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract               This research aims to study and measure the correlation and influence relationships between competitive pressures Represented by its dimensions (product competition, market share competition, similar companies, technological change, price competition, government regulations and policies, as well as promotion and distribution channels), and strategic performance in its dimensions (competitive performance, operational performance, and performance Financial), and the main research problem was that the private commercial banking sector in Iraq is witnessing intense competition between banks in general and commercial banks specifically, and the competitive pressures generated by the competition between those banks and its impact on strategic performance. By conducting a simple comparison, we find that the structure of the sector Banking in neighboring countries such as Saudi Arabia consists of a group of (30) banks, in Turkey it consists of (43) banks, and in Iran (30) banks. If the comparison is made to a country like the United Kingdom, it has (54) banks, while in Iraq it has (77) operating banks. Through this comparison, the extent of competition between banks operating in Iraq becomes clear. The researcher adopted the descriptive analytical approach to complete the research. The field of research was the banking sector, specifically private commercial banks, which are (Bank of Baghdad, Commercial Bank of Iraq, Iraqi Investment, National Bank of Iraq, Iraqi Credit, Economy Bank for Investment and Finance,  Sumer Commercial, Business Gulf, Mosul for Development and Investment, and the Iraqi Federation(, and the questionnaire was the main tool that the researcher adopted to collect data and information regarding the responses of the research sample, as the research community consisted of (343) individuals from senior and middle leadership. In the aforementioned banks, the sample reached (200) respondents, and the number of returned questionnaires suitable for statistical analysis reached (177) questionnaires. For the purpose of analyzing the data, the program (SPSS.V26) was used, and among the statistical methods used in the analysis process (arithmetic mean, standard deviation, coefficient of variation, simple linear regression analysis), and the most prominent results reached are the presence of a correlation and influence on the degree of morality between competitive pressures and strategic performance.